How does digital governance improve natural resource utilization efficiency? Configuration analysis based on the TOE framework - Shijia Zhang; Xiaojuan Cao (Humanities & Social Sciences Communications)
Abstract As global resource pressures and the demand for environmental sustainability increase, effectively improving natural resource utilization efficiency (NRUE) has become a critical challenge for countries worldwide. In this context, digital governance is gradually emerging as a key solution to this issue. By leveraging data analysis and intelligent decision support systems, digital governance enables the precise management of natural resources, which helps to increase resource utilization efficiency and provides strong support for achieving global sustainable development goals. This paper first analyses the spatial‒temporal distribution characteristics of China’s NRUE from 2018 to 2022. Then, on the basis of the TOE framework, this paper uses the dynamic QCA method to comprehensively analyze the digital governance strategies for improving the NRUE. The research results indicate that (1) during the study period, China’s NRUE steadily improved, showing a gradient distribution from east to west. (2) Digital infrastructure, digital technological innovation, digital governance capacity of the government, digital economic development, and digital inclusive finance have played significant roles in improving the NRUE, but no single factor is sufficient to be a necessary condition for high NRUE. (3) Four key models for enhancing the NRUE are identified: organization-technology driven, technology-environment driven, organization-environment driven, and holistic synergy driven. (4) In the temporal dimension, the consistency level of the five configurations showed an overall downwards trend in 2020, which was likely influenced by the public health crisis of the COVID-19 pandemic. (5) In the spatial dimension, there are regional differences in the coverage of each configuration. This paper expands the understanding of the transformation of government roles and functions in the digital economy era and provides a new theoretical framework for digital governance, aiming to promote the further improvement of the NRUE.